2022
DOI: 10.1108/jpmh-06-2021-0080
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic mental health inequalities and mental health policies in England 1999-2020

Abstract: Purpose This paper presents a thematic synthesis of mental health policies published in England from 1999 to 2020. Design/methodology/approach This paper aims to present a thematic synthesis of mental health policies published in England from 1999 to 2020. The authors specifically focus on ethnicity-related mental health issues highlighted in policies, policy recommendations and performance measurements of policy implementation. Findings Findings from this synthesis demonstrate that ethnic mental health in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…The recent mental health policies in Scotland ( 42 ), Wales ( 43 ) and Northern Ireland ( 44 ) all highlight the importance of addressing inequalities in order to promote mental health. In their review of mental health policies in England from 1999 to 2020, Hussain et al ( 45 ) report that over this period, ethnic mental health inequalities remain comparable and policy recommendations have also remained largely the same.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent mental health policies in Scotland ( 42 ), Wales ( 43 ) and Northern Ireland ( 44 ) all highlight the importance of addressing inequalities in order to promote mental health. In their review of mental health policies in England from 1999 to 2020, Hussain et al ( 45 ) report that over this period, ethnic mental health inequalities remain comparable and policy recommendations have also remained largely the same.…”
Section: Discussionmentioning
confidence: 99%
“…A few people mentioned that they missed traveling to go on holiday, and others were affected by not being able to travel within the country due to the restrictions as they had no family or friends nearby to promote mental health. In their review of mental health policies in England from 1999 to 2020, Hussain et al (45) report that over this period, ethnic mental health inequalities remain comparable and policy recommendations have also remained largely the same.…”
Section: Travelmentioning
confidence: 99%
“…Moreover, V.I. has been associated with poorer mental health outcomes (Kempen et al, 2012;Zhang et al, 2013;van der Aa et al, 2015;Frank et al, 2019), but there is also 10.3389/fpsyg.2024.1359074 Frontiers in Psychology 13 frontiersin.org evidence of mental health inequalities among adults from minority ethnic communities in the UK in terms of diagnoses of mental health conditions and experiences of mental health support services (Grey et al, 2013;Hussain et al, 2022). Research with adults with disabilities who are LGBTQI+ found that they may feel uncomfortable to disclose their status to authorities and personal carers, due to concerns that their status may impact on the care provided to them if an assessor or personal carer has strict religious beliefs (Abbott et al, 2017).…”
Section: Other Considerationsmentioning
confidence: 99%
“…Whilst underexplored, MEC adults with V.I. may experience additional challenges relating to mental health, with evidence of mental health inequalities among MEC adults in the UK, both in terms of diagnoses of mental health conditions and experiences of support services ( 23 , 24 ). This could reflect experiences of stigma and discrimination amongst MEC adults with V.I.…”
Section: Introductionmentioning
confidence: 99%